A Four-Nation Comparison of Kinship Care in the UK: The Relationship between Formal Kinship Care and Deprivation. Issue 4 (6th July 2018) - McCartan, Claire; Bunting, Lisa; Bywaters, Paul; Davidson, Gavin; Elliott, Martin; Hooper, Jade
Abstract : The practice of extended family and friends helping to care for children when their parents are unable to is an enduring tradition in many cultures. Kinship care provides the largest proportion of out of home care in Western society but many of these carers experience poverty and deprivation, and do not receive comparable levels of support, financial or professional, to other placement types. This study provides UK evidence for the relationship between kinship care and deprivation and examines how the welfare state frames kinship care in policy and practice.